The safety of sotagliflozin in the therapy of diabetes mellitus type 1 and type 2: A meta-analysis of randomized trials - Zhou, Feifei; Du, Nannan; Zhou, Lulin; Wang, Chenxi; Ren, He; Sun, Qiang (Frontiers in Endocrinology, 2022)
Diabetes mellitus has become a shocking threat in the contemporary era. The objective of this study was to analyze the safety of sotagliflozin in patients with DM systematically and intuitively. On November 15, 2021, literature retrieval was performed on PubMed, Web of Science, EBSCO, and Cochrane libraries. The meta-analysis results included genital mycotic infection, related-to-acidosis events, and other related adverse events, including diarrhea, severe nocturnal hypoglycemia event, and volume depletion. Moreover, the patient-treated years analyzed in the study were 12 weeks, 24 weeks, and 52 weeks, respectively, for type 1 diabetes, and were 12 weeks, 22 weeks, and 52 weeks, respectively, for type 2 diabetes. The results of this meta-analysis illustrated that sotagliflozin could increase the risk of genital mycotic infection for patients with T1D and T2D (RR: 3.49, 95% Cl: 2.54-4.79, p < 0.001; RR: 2.83, 95% Cl: 2.04-3.93, p < 0.001; respectively). Moreover, sotagliflozin could increase the risk of events related to acidosis in the patients of T1D, including acidosis-related adverse events, positively adjudicated diabetic ketoacidosis, acidosis-related event, and diabetic ketoacidosis (RR: 7.49, 95% Cl: 3.20-17.52, p < 0.001; RR: 6.05, 95% Cl: 2.56-14.30, p < 0.001; RR: 4.83, 95% Cl: 3.13-7.45, p < 0.001; RR: 8.12, 95% Cl: 3.06-21.52, p < 0.001; respectively). In the patients of T2D, sotagliflozin could not increase the risk of DKA (RR: 1.30, 95% Cl: 0.34-4.99, p = 0.70). As for the other related adverse events, sotagliflozin was found to be a risk factor for diarrhea and volume depletion in T1D patients (RR: 1.44, 95% Cl: 1.09-1.90, p = 0.01; RR: 2.50, 95% Cl: 1.33-4.69, p < 0.01; respectively) and T2D patients (RR: 1.44, 95% Cl: 1.26-1.64, p < 0.001; RR: 1.25, 95% Cl: 1.07-1.45, p < 0.01; respectively). This meta-analysis showed that the adverse events of sotagliflozin were tolerable to patients with DM, in terms of the incidence of genital mycotic infection, related-to-acidosis events, diarrhea, volume depletion, and severe nocturnal hypoglycemia events. In addition, the subgroup analysis of sotagliflozin dosage is considered to have great clinical significance for future guidance of sotagliflozin application in patients with DM.